The Upper Palaeolithic Lithic Industry of Nazlet Khater 4 (Egypt): Implications for the Stone Age/Palaeolithic of Northeastern. - (:unkn) unknown (My University, 2011)
Between Marine Isotope Stage (MIS) 4 and 2, Northeast Africa witnessed migrations of Homo sapiens into Eurasia. Within the context of the aridification of the Sahara, the Nile Valley probably offered a very attractive corridor into Eurasia. This region and this period are therefore central for the (pre)history of the out-of-Africa peopling of modern humans. However, there are very few sites from the beginning of the Upper Palaeolithic that document these migration events. In Egypt, the site of Nazlet Khater 4 (NK4), which is related to ancient H. sapiens quarrying activities, is one of them. Its lithic assemblage shows an important laminar component, and this, associated with its chronological position (ca. 33 ka), means that the site is the most ancient Upper Palaeolithic sites of this region. The detailed study of the Nazlet Khater 4 lithic material shows that blade production (volumetric reduction) is also associated with flake production (surface reduction). This technological duality addresses the issue of direct attribution of NK4 to the Upper Palaeolithic.
Keywords: African Research